2019
DOI: 10.1055/s-0039-1681025
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of the Single Step Questionnaire in Pectus Excavatum Patients is Phase Dependent

Abstract: Introduction Pectus excavatum (PE) is the most common chest wall deformity. Patients with PE may have cosmetic complaints, restricted physical capabilities, or both and may seek surgical correction. One method to assess satisfaction after surgery is the single step questionnaire (SSQ). Although the developers state that the SSQ produces a stabile score and only needs to be used once, we hypothesized that the score may depend on point in time after surgery. Materials and Methods One hundred and eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Other patients reported that they wouldn't consider going through another procedure again due to pain. It has been reported that pain is a significant post-operative factor influencing satisfaction [13]. In our study, most patients that reported dissatisfaction complained of postoperative pain and all had surgery before 2017, the year our institution started using intra-operative cryoablation.…”
Section: Accepted Manuscriptmentioning
confidence: 62%
See 2 more Smart Citations
“…Other patients reported that they wouldn't consider going through another procedure again due to pain. It has been reported that pain is a significant post-operative factor influencing satisfaction [13]. In our study, most patients that reported dissatisfaction complained of postoperative pain and all had surgery before 2017, the year our institution started using intra-operative cryoablation.…”
Section: Accepted Manuscriptmentioning
confidence: 62%
“…It consisted of 15 questions assessing general health, exercise capacity, chest appearance, self-esteem, pain, and satisfaction after the operation. A score of more than 41 is considered satisfactory [13]. One study documented satisfaction at different post-operative times and noticed a significant difference in the scores depending on the time the survey was answered after surgery showing an increase in patient satisfaction over time [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were similar for any of the procedures involved (Nuss/MARPE and Ravitch) and were more prominent in the interval 6 weeks to 6 months after surgery. 19…”
Section: Discussionmentioning
confidence: 99%
“…Pre-school repair can avoid intramural sports limitations and possible discrimination as removing the plate before school starts. So, tting into the group and having a "normal look" seems to be important in adolescence, where peer pressure is high [30].…”
Section: Commentmentioning
confidence: 99%